Framework of Intrinsic and Extrinsic Motivators of Knowledge Sharing: A case of Training Institutes of an Oil and Gas Company in Malaysia - Amin, A.; Hassan, M.F.; M Ariffin , Mazeyanti (2010)
Knowledge sharing is vital for the success of Knowledge Management (KM) initiatives. But it is inconceivable to flourish knowledge sharing without individual's motivation to share his knowledge. Individuals are motivated through intrinsic as well as extrinsic motivators. Due to this reason researchers have underlined the importance of extrinsic rewards and Organization Citizenship Behavior (OCB) to influence individual's decision to share his knowledge. Extrinsic rewards dwell in extrinsic motivation whereas OCB represents intrinsic motivation. The relationships of these variables with knowledge sharing have been tested in past research works, however there are a number of limitations which need to be addressed. Using the case of training institutes of an oil and Gas Company in Malaysia, the aim of the study is to propose a framework of intrinsic and extrinsic motivators of knowledge sharing. The proposed framework will overcome the limitations in the literature by revisiting the impact of extrinsic rewards and OCB on knowledge sharing. The proposed framework has incorporated intrinsic (OCB) and extrinsic motivators (extrinsic rewards) in the Theory of Reasoned Action (TRA). Five major and in total 15 hypotheses have been tested. The data was gathered from the knowledge workers, working as trainers and facilitators, at three training institutes of an oil and gas company. Questionnaire method was used to gather data. Later the data was tested using regression analysis through SPSS. The results have shown that OCB is a very strong predictor of knowledge sharing behavior, whereas extrinsic reward's affect on individual's intention to share his knowledge is moderate. The study will help us to understand the role of individual's intrinsic (i.e. OCBs) and extrinsic motivators (i.e. extrinsic rewards) to affect his decision to share his knowledge. The study will also help the theorists and practitioners to develop strategies to foster knowledge sharing in their organizations.